Vart försvann mitt perfekta datamaterial? - Lärdomar från att utföra en undersökning i praktiken - Deros,Emily (2020)
Back in the mid 1900s, Zimbabwe was one of the most developed states in Africa with well-established infrastructure and a flourish economy thanks to inter alia agricultural exports and industries, among other things. A survey has been performed in order to evaluate the socio-economic conditions in Zimbabwe. This paper uses the fore mentioned study to investigate the challenges and problems that can emerge in research. Starting with a short description of how the survey has been performed, followed by modes of input and processing of data into a yearly report are presented. The results of the survey are presented with a report available in Appendix A, with a short summary of the report available in section 4 of this paper. Challenges that arose during the study and how they were dealt with is then discussed. This discussion reveals the challenges of retroactively constructing a survey design when information is missing on how the sample has been drawn. Furthermore, the challenge of comparing economic changes over time is presented and is followed by a discussion regarding the trade-offs that had to be made in order to limit the measurement error.